Literature Review: The Effectiveness of the Implementation of Restorative Justice in the Criminal Justice System in Indonesia - Irwanto, Irwanto; santosa, Tomi Apra; Ghoni, Abdul; Jaya, Alwi; Hartawati, Andi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study presents a literature review on the effectiveness of the implementation of restorative justice in the criminal justice system in Indonesia. Restorative justice has emerged as an alternative approach to resolving criminal cases by emphasizing reconciliation, victim-offender dialogue, and community involvement rather than solely focusing on retributive punishment. Through a systematic review of relevant national and international literature published between 2010 and 2024, this study explores the theoretical foundations, legal frameworks, practical applications, and challenges of restorative justice within the Indonesian context. The findings indicate that restorative justice contributes to reducing prison overcrowding, enhancing victims’ satisfaction, and fostering community harmony. However, its effectiveness is often constrained by limited legal awareness, inconsistent implementation, and institutional resistance within the conventional justice system. This review concludes that restorative justice in Indonesia holds significant potential to strengthen a more humane and participatory criminal justice system, provided that it is supported by stronger regulatory frameworks, adequate resources, and comprehensive training for law enforcement officers.